Formulasi dan evaluasi sediaan sabun cair hidrosol kulit bawang sebagai antibakteri - Rianti, Dian Ratna; Sofyan, Octariana; Wijaya, Andi (Sasambo Journal of Pharmacy, 2025)
Onion peels (shallots and garlic) can be developed into valuable products. One approach to utilizing onion peels is by processing them into hydrosol, which can be used in liquid soap formulations. The aim of this study is to evaluate the characteristics of liquid soap derived from the hydrosol of onion peel waste. Onion peels was processed into hydrosol by water distillation method. Hydrosol was subjected to phytochemical screening and formulated into liquid soap dosage form. Soap was made into 3 formulas with different concentrations of hydrosol in formulas F1 (5%), F2 (7.5%), and F3 (10%). The liquid soap was evaluated for characteristics including organoleptic test, pH, foam height, viscosity, and antimicrobial activity. The results of the hydrosol phytochemical screening test showed the presence of saponins and alkaloids. The results of the liquid soap organoleptic test showed that F1, F2, and F3 gave a clear color, liquid shape, and aromatic odor. F1 liquid soap pH 6.51, F2 6.44 and F3 6.43; foam height 2.50 cm, 2.10 cm, 2.33 cm; and viscosity F1 316 m.Pa.s, F2 99.99 m.Pa.s and F3 99.99 m.Pa.s. The results of the antimicrobial test of negative control (base), F1, F2, and F3 produced a clear zone. The characteristics of the soap produced provide good organoleptics, pH and foam stability. Hydrosol concentration affects the viscosity produced. Onion peel liquid soap F3 exhibit the highest average diameters of the inhibition zones 10,02Â±0,49 mm, and is categorized as having strong antimicrobial properties.